Attitudes towards whistleblowers, organizational commitment, ethical climate principles, and self-effi cacy as determinants of fraud disclosures - Nur Hayati; putri wulanditya (Universitas Hayam Wuruk Perbanas, 2018)
Whistle-blowing is one of pro-social action done by organization members to give directions, procedures, or policies that have corrective impact on the organizations. The brave action to disclose fraud is determined by internal and external factors of individuals. This research is conducted to test factors that infl uence people to conduct whistleblowing, such as attitudes towards whistleblowers, ethical climate-principles, organization commitment, and self-effi cacy. This research also has objective to test the applications of Theory of Planned Behavior (TPB) and Pro-social Organizational Behavior (POB) particularly related to fraud. The research methodology is conducted using questionaire and analyzed using Multiple Regression. Results of the research show that attitudes towards whistleblowers, ethical climate principles, organizational commitments, and self-effi cacy have a signifi cant effect on the intention to conduct whistle-blowing.